Between Hamka and Nursi: enlightening the locals via Quranic exegesis - Abdul Jalil, Mohd. Noh; Mamat, Ismail (2020)
This paper discusses the contribution of two great scholars in the Muslim world, Bediʿuzzaman Saʿid Nursī (d.1960) and Haji ʿAbdul Malīk bin ʿAbdul Karīm ʿAmrullah (HAMKA) (d.1981). They contributed immensely to their communities in Turkey and Indonesia. Both scholars produced magnum opus on the meanings and interpretations of the Qur’ān. This article examines the contents of Saʿid Nursī’s Risale-i Nur and HAMKA’s Tafsīr al-Azhar respectively. Besides, this article also focusing on Quranic exegesis methodologies adopted by both scholars. The paper employs textual analysis and comparative study on Risale-i Nur and Tafsīr al-Azhar, supported by other related written materials on the topic. This paper concludes that Saʿid Nursī and Hamka employ Quranic exegesis as a medium to make Islām understandable and practical in their locality. It is evident that certain methodologies of the Quranic exegesis they adopted in both Risale-i Nur and Tafsīr al-Azhar served as the daʿwah tools in an efforts to bring Islam closer to the local community